Diagnostic Approach to Acute Liver Failure in Children: A Position Paper by the SIGENP Liver Disease Working Group. Issue 5 (May 2021) - Di Giorgio, A.; Bartolini, E.; Calvo, P.L.; Cananzi, M.; Cirillo, F.; Della Corte, C.; Dionisi-Vici, C.; Indolfi, G.; Iorio, R.; Maggiore, G.; Mandato, C.; Nebbia, G.; et al.
Abstract: Acute liver failure (ALF) is a clinical condition characterized by the abrupt onset of coagulopathy and biochemical evidence of hepatocellular injury, leading to rapid deterioration of liver cell function. In children, ALF has been characterized by raised transaminases, coagulopathy, and no known evidence of pre-existing chronic liver disease; unlike in adults, the presence of hepatic encephalopathy is not required to establish the diagnosis. Although rare, ALF has a high mortality rate without liver transplantation (LT). Etiology of ALF varies with age and geographical location, although it may remain indeterminate in a significant proportion of cases. However, identifying its etiology is crucial to undertake disease-specific management and evaluate indication to LT. In this position statement, the Liver Disease Working Group of the Italian Society of Gastroenterology, Hepatology and Nutrition (SIGENP) reviewed the most relevant studies on pediatric ALF to provide recommendations on etiology, clinical features and diagnostic work-up of neonates, infants and children presenting with ALF. Recommendations on medical management and transplant candidacy will be discussed in a following consensus conference.